Sebuah Studi Daya Dukung dan Penurunan Tiang Bor Menggunakan PLAXIS 3D Berdasarkan Data N-SPT - Pratiwi, Desti Santi; Winoto, Ghozi Warsih (JURNAL RIVET, 2025)
The foundation is essential in construction, as it transfers the building's load to the ground. This study evaluates the axial and lateral bearing capacities and settlement of bored pile foundations using PLAXIS 3D with Mohr-Coulomb and Hardening Soil material models. The results are compared with field tests from the PDA and Static Loading Tests. The Results show that the choice of material model significantly influences bearing capacity and settlement. The highest axial bearing capacity recorded was 7,384.41 kN, and the lateral capacity was 393 kN, achieved with the Mohr-Coulomb model and Linear Elastic pile material. The settlement results from PLAXIS 3D were generally lower than those from the PDA Test, with a deviation of 5–13%. In contrast, the axial bearing capacities from PLAXIS 3D exceeded those from the Static Loading Test by about 1–14%. This study underscores the importance of selecting the appropriate soil constitutive model to ensure that numerical simulations reflect real-world conditions accurately.